NOD2 contributes to cutaneous defense against Staphylococcus aureus through [alpha]-toxin-dependent innate immune activation - Hruz, Petr; Zinkernagel, Annelies S; Jenikova, Gabriela; Botwin, Gregory J; Hugot, Jean-Pierre; Karin, Michael; Nizet, Victor; Eckmann, Lars (Proceedings of the National Academy of Sciences - PNAS, 2009)
Staphylococcus aureus is a major cause of community-acquired and nosocomial infections including the life-threatening conditions endocarditis, necrotizing pneumonia, necrotizing fasciitis, and septicemia. Toll-like receptor (TLR)-2, a membrane-bound microbial sensor, detects staphylococcal components, but macrophages lacking TLR2 or both TLR2 and TLR4 remain S. aureus responsive, suggesting that an alternative microbial recognition receptor might be involved. The cytoplasmic sensor nucleo-tide-binding oligomerization domain containing (NOD) 2/caspase recruitment domain (CARD) 15 detects muramyl dipeptide from bacterial peptidoglycans and mediates cytokine responses to S. aureus in vitro, but the physiological significance of these observations is not well defined. Here we show that NOD2-deficient mice exhibit a delayed but ultimately exacerbated ulcerative response and impaired bacterial clearance after s.c. infection with S. aureus. NOD2-dependent recognition of S. aureus and muramyl dipeptide is facilitated by α-toxin (α-hemolysin), a pore-forming toxin and virulence factor of the pathogen. The action of NOD2 is dependent on IL-1β-amplified production of IL-6, which promotes rapid bacterial killing by neutrophils. These results significantly broaden the physiological importance of NOD2 in innate immunity from the recognition of bacteria that primarily enter the cytoplasm to the detection of bacteria that typically reside extracellularly and demonstrate that this microbial sensor contributes to the discrimination between commensal bacteria and bacterial pathogens that elaborate pore-forming toxins. [PUBLICATION ABSTRACT]